Relativistic quantum physics : from advanced quantum mechanics to introductory quantum field theory - Ohlsson, Tommy (Cambridge, UK : Cambridge University Press, 2011)
"Quantum physics and special relativity theory were two of the greatest breakthroughs in physics during the twentieth century and contributed to paradigm shifts in physics. This book combines these two discoveries to provide a complete description of the fundamentals of relativistic quantum physics, guiding the reader effortlessly from relativistic quantum mechanics to basic quantum field theory. The book gives a thorough and detailed treatment of the subject, beginning with the classification of particles, the Klein-Gordon equation and the Dirac equation. It then moves on to the canonical quantization procedure of the Klein-Gordon, Dirac and electromagnetic fields. Classical Yang-Mills theory, the LSZ formalism, perturbation theory, elementary processes in QED are introduced, and regularization, renormalization and radiative corrections are explored. With exercises scattered through the text and problems at the end of most chapters, the book is ideal for advanced undergraduate and graduate students in theoretical physics"--
Machine generated contents note: 1. Introduction to relativistic quantum mechanics; 2. The Klein-Gordon equation; 3. The Dirac equation; 4. Quantization of the non-relativistic string; 5. Introduction to relativistic quantum field theory: propagators, interactions, and all that; 6. Quantization of the Klein-Gordon field; 7. Quantization of the Dirac field; 8. Maxwell's equations and quantization of the electromagnetic field; 9. The electromagnetic Lagrangian and introduction to Yang-Mills theory; 10. Asymptotic fields and the LSZ formalism; 11. Perturbation theory; 12. Elementary processes of quantum electrodynamics; 13. Introduction to regularization, renormalization, and radiative corrections; Appendix; Index.
Includes bibliographical references and index.
Keywords: Quantum theory